Effect of zeolite naa additive on the absorption refrigeration unit - B., Badarullah; Abdul Halim, Abdul Razik; Aainaa Izyan, Nafsun (IOP Publishing, 2020)
Absorption refrigeration has a potential to become among the most effective refrigeration unit due to low power consumption and eco-friendly benefits. However, the problem of relatively lower performance compared to the compressor refrigeration unit has increased the efforts for improvements including working fluid modification and addition of special additive. The purpose of this study was to investigate the effects by adding Zeolite NaA as an additive in the ammonia/water solution in the bench-scale absorption refrigeration system. The additive contains of certain chemicals such as sodium hydroxide, sodium aluminate and sodium metacilicate. The additive was added with different concentrations in the range of 0.2 mM to 0.001 M. From the experiment, the highest COP was calculated to be 6.3 with 0.001 M of additive, while the lowest cooling box temperature was recorded to be 20oC with 0.6 mM additive and 1.5 of COP. The ratio of ammonia and water solution was 30/70% by volume for the obtained result which could be subjected to further research.